THE RELATIONSHIP BETWEEN LEARNING EXPERIENCES ON ENVIRONMENTAL CHANGE AND ENVIRONMENTAL LITERACY OF GRADE X HIGH SCHOOL STUDENTS - Damayanti, Rosita; Suhartini, Suhartini (Universitas Negeri Yogyakarta, 2025)
A learning experience is one of the key demands in science learning. Biology, as part of science, is also expected to help develop students' environmental literacy. This study aims to determine the relationship between learning experiences on environmental change materials and environmental literacy among grade X students of SMAN 1 Sleman, in the context of global warming. This study is an ex-post facto correlation study using mixed methods. The study was conducted at SMAN 1 Sleman with a sample of 130 grade X students. Data collection used a Likert-scale questionnaire, multiple-choice tests, and essays, supported by interviews with teachers and students. The data analysis technique in this study used descriptive statistical analysis and the Pearson Product-Moment correlation test. From the results of the correlation test, it was found that there was a positive and significant relationship between learning experiences on environmental change material and environmental literacy in the context of global warming. This study aims to provide insights into the relationship between learning experiences and students' environmental literacy. Teachers can use the results of this study as a basis for creating meaningful learning experiences for students.